(untitled) (Bangladesh Journal of Medicine, 2026)
Background: Hepatitis B Virus (HBV) infection constitutes a significant occupational hazard for healthcare workers (HCWs), particularly intern doctors who are at the frontline of patient care and perform high-risk procedures. Vaccination is the most effective preventive measure, and postvaccination serological testing for anti-HBs antibodies is crucial to confirm seroprotection .This study aimed to assess the HBV vaccination status and determine the seroprotection rate among intern doctors in a Medical College of Bangladesh. Methods: A cross-sectional study was conducted from January to March 2023 among 200 intern doctorsin the Department of Gastroenterology, Rangpur Medical College Hospital ofBangladesh. Participants were interviewed using a structured questionnaire to ascertain their HBV vaccination history. Those with a complete vaccination record (three or more doses) were included for serological testing. Individuals with known immunodeficiency disorders, chronic illnesses, or on immunosuppressive therapy were excluded. A total of 159 interns were confirmed as vaccinated. Among them, 150 consented to provide a blood sample for quantitative anti- HBs titer measurement via Chemiluminescent Microparticle Immunoassay (CMIA). Results: The vaccination coverage among the intern doctors was 79.5% (159/200). Among the 150 interns whose anti-HBs titers were analyzed, 132 (88.0%) had protective antibody levels (anti-HBs e”10 mIU/mL). The mean anti-HBs titer was 287.6 mIU/mL (Range: 2.1 to >1000 mIU/mL). However, 18 (12.0%) interns were identified as non-responders (anti-HBs <10 mIU/mL) despite completing the primary vaccination series. No significant correlation was found between the time since last vaccination and antibody titer within this short follow-up duration. Conclusion: Although a high rate of vaccination coverage was observed, a concerning 12% of vaccinated intern doctors lacked adequate seroprotection against HBV, leaving them vulnerable to a life-threatening occupational infection. This underscores the critical necessity of mandatory post-vaccination serological testing (anti-HBs titer) for all healthcare workers following primary immunization. Non-responders must be identified and managed with additional vaccine doses or strict adherence to universal precautions to prevent this preventable professional hazard. Bangladesh J Medicine 2026; 37(2): 137-142